Beispiel Nr: 11
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ \frac{1}{2}x^3-3x^2+5x =0\\ \\ \textbf{Rechnung:} \\ x( \frac{1}{2}x^2-3x+5)=0 \Rightarrow x=0 \quad \vee \quad \frac{1}{2}x^2-3x+5=0\\ \frac{1}{2}x^{2}-3x+5 =0\\ x_{1/2}=\displaystyle\frac{+3 \pm\sqrt{\left(-3\right)^{2}-4 \cdot \frac{1}{2} \cdot 5}}{2\cdot\frac{1}{2}}\\ x_{1/2}=\displaystyle \frac{+3 \pm\sqrt{-1}}{1}\\ \text{Diskriminante negativ keine Lösung} \\ \underline{x_1=0; \quad1\text{-fache Nullstelle}} \\$